Reference standard for the uncertainty estimation of X–ray Computed Tomography measurements of complex macro-and micro-geometries. Issue 1 (October 2021) - Albajez, J A; Nuño, S; Díaz, L C; Gallardo, D; Yagüe, J A; Jiménez, R; Torralba, M
Abstract: Traditionally, measuring both macro and micro geometries with a single device has been challenging in metrology. Coordinate Measuring Machines (CMM) are common devices for the inspection of large features, while optical microscopes can achieve resolutions in the order of micrometers in small areas. X-Ray Computed Tomography (XCT) has become a solution not only to characterize both micro and macro geometries, but also to inspect internal features without destroying the sample. In this field, various reference standards have been developed in order to verify the capabilities of XCT systems, these artefacts include geometrical features or profiles for roughness inspection. This paper shows the design and develompent of a reference standard for XCT test which includes internal and external geometrical features and profiles for macro and micro geometrical inspection. The model is manufactured by additive manufacturing (AM), easing the process of fabrication of the artefact and allowing to test the capabilities of this technology to produce reference standards.